Enzymatic synthesis of capric acid-rich structured lipids and their effects on mice with high-fat diet-induced obesity - Martínez-Galán, Julián Paul; Ontibón-Echeverri, Catalina María; Campos Costa, Mariana [UNESP]; Batista-Duharte, Alexander [UNESP]; Guerso Batista, Vinicius [UNESP]; Mesa, Victoria; Monti, Rubens [UNESP]; Veloso de Paula, Ariela [UNESP]; Martins Baviera, Amanda [UNESP] (Elsevier, 2021)
The objective of this study was to produce structured lipids (SLs) by enzymatic acidolysis using Rhizopus oryzae lipase covalently immobilized in a low-cost material. Grape seed oil was used to synthesize SLs containing the medium-chain fatty acid (C10:0) capric acid. SL synthesis led to 38.8% medium-chain fatty acid incorporation with 5 reuses of the enzymatic derivative. The reaction conditions for the synthesis of MLM-TAGs (triacylglycerols with one long- and two medium-chain acyl residues) were at a molar ratio of fatty acid:oil of 3:1, performed at 40 °C and lipase immobilized load of 5% (w/w). The in vivo effects of SLs were studied in Swiss mice fed premade diets: control (C) diet, high-fat diet (HFD) with 100% lipid content as lard, HFD with 50% lipid content as grape seed oil (HG) or HFD with 50% lipid content as capric acid-containing SLs produced from grape seed oil (HG-MCT). Mice from HG and HG-MCT groups had decreases in body weight gain and reductions in the weights of white adipose tissues. In addition, HG and HG-MCT mice had low plasma levels of glucose and total cholesterol, and improvements in the glucose tolerance. HG and HG-MCT diets have remarkable antioxidant properties, since low plasma levels of TBARS (thiobarbituric acid reactive substances, biomarkers of lipid peroxidation) were found in mice fed these diets. Interestingly, TBARS levels in HG-MCT mice were further decreased than values of HG mice. Mice fed HG and HG-MCT diets also showed preservation in the activity of the antioxidant enzyme paraoxonase 1. Both HG and HG-MCT diets promoted reduction of IL-6 and IL-10 production by splenocytes. The capric acid-containing SLs produced from grape seed oil emerges as a functional oil capable to mitigate obesity complications resulting from oxidative stress and inflammation.
Keywords: Enzymatic acidolysis; Glucose intolerance; Inflammation; Lipase; Obesity; Oxidative stress; Structured lipids